2022
DOI: 10.1038/s41598-022-12239-9
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse fibrosis and repolarization disorders explain ventricular arrhythmias in Brugada syndrome: a computational study

Abstract: In this work, we reported a computational study to quantitatively determine the individual contributions of three candidate arrhythmic factors associated with Brugada Syndrome. In particular, we focused our analysis on the role of structural abnormalities, dispersion of repolarization, and size of the diseased region. We developed a human phenomenological model capable of replicating the action potential characteristics both in Brugada Syndrome and in healthy conditions. Inspired by physiological observations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In our model the intensity of I T O is increased when d 0 w is decreased. The minimal d 0 w used in our simulations (d 0 w = 0.3) caused irreversible AP dome loss in the isolated myocyte model, whereas the maximal (d 0 w = 0.5) caused a delayed dome AP morphology [5].…”
Section: Myocyte Modelmentioning
confidence: 90%
See 2 more Smart Citations
“…In our model the intensity of I T O is increased when d 0 w is decreased. The minimal d 0 w used in our simulations (d 0 w = 0.3) caused irreversible AP dome loss in the isolated myocyte model, whereas the maximal (d 0 w = 0.5) caused a delayed dome AP morphology [5].…”
Section: Myocyte Modelmentioning
confidence: 90%
“…To perform the simulations, we employed our previously published phenomenological model of ventricular myocytes [4][5][6]. With different sets of parameters, the model reproduces the electrophysiological properties of both epicardium, endocardium and midmyocardium.…”
Section: Myocyte Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous computational work of our group regarding BrS, we related structural and electrophysiological abnormalities to a possible mechanism of arrhythmia in a computational model of BrS. 87,103 We observed that the likelihood of arrhythmia was a function of the structural alteration and electrophysiological alteration and demonstrated that the plane defined by these two parameters defines regions of low and high probability of arrhythmia. The application of this model to clinical risk stratification context requires the identification of which physiological quantities are related to the modeled structural and electrophysiological alterations (e.g., EGM fractionation as a marker of structural alteration), and how their values are related to the values modeled in the computational setup.…”
Section: Definition Of the Arrhythmic Riskmentioning
confidence: 93%
“…mulation, where the diffusivity values were selected to replicate time intervals corresponding to complete atrial activation [8], atrioventricular conduction [9], and complete ventricular activation [10]. For the definition of the ionic current (I ion ), we adopted our previously published phenomenological model [11][12][13], which we fitted to the electrophysiological properties of the different types of cardiac cells. The fitting procedure is aimed at reproducing the main characteristics of experimental action potential morphology and action potential duration, and conduction velocity steady-state restitution curves.…”
Section: Heart Modelmentioning
confidence: 99%